Appendiceal Diverticulitis Mimics Cecal Diverticulitis Diagnosed Preoperatively - Phu Cuong Pham; Hoang Anh Thi Van; Van Trung Hoang; The Huan Hoang; Duc Duy Nguyen; Duc Thanh Hoang (SAGE Publishing, 2024)
Appendiceal diverticulitis is an uncommon condition that clinically resembles acute appendicitis. However, it is an incidental finding in histopathological studies and is rarely diagnosed preoperatively by imaging studies. In this article, we present the clinical and imaging findings of a male patient presenting with right upper quadrant pain with a preoperative imaging diagnosis of appendiceal diverticulitis. He underwent laparoscopic appendectomy and confirmed the diagnosis of appendiceal diverticulitis. This is a rare preoperative diagnosis. The management is often like typical appendicitis which is appendectomy. It is important to differentiate it from diverticulitis of the small intestine or colon because these diseases usually require only conservative treatment.